Variation of abductor pollicis longus tendons in cadavers - Jain, R. K.; Mantri, Nihit; Mandlecha, P. (International Journal of Research in Orthopaedics, 2018)
Background: First extensor compartment of the wrist comprises of abductor pollicis longus and extensor pollicis brevis. It helps in movement and stabilization of thumb. Variations in the number of tendons of APL muscle may be asymptomatic and often incidental finding. Stenosing tenosynovitis of the first dorsal compartment of the wrist or de Quervains disease is a commonly encountered debilitating condition of the wrist. Methods: This cadaveric study was done on 40 forearms in 20 cadavers available in Department of anatomy and forensic medicine at our institute. The muscles of extensor compartments were dissected, extensor retinaculum split over first extensor compartment, tendons of APL exposed. Study period from February-2017 to February-2018. Results: There were 6 female and 14 male cadavers. The APL muscle was found with a single tendon in 2, double in 30, triple in 8. There were variations in the insertion of the APL tendon as well. In all hands, the APL tendon had insertion into the first metacarpal bone and in 20 hands (50%), it had second insertion into the trapezium. Conclusions: Variation of APL muscle insertion in the Indian population and two or more tendinous slips attached commonly to the first metacarpal base and the trapezium may be the cause of treatment failure in DQT and cause of Trapeziometacarpal arthritis. Further studies needs to be done for further evaluation.